Safety, Efficacy and Prognostic Benefit of Atrial Fibrillation Ablation in Heart Failure with Preserved Ejection Fraction. Issue 1 (2022) - Johner, Nicolas; Namdar, Mehdi; Shah, Dipen C
No abstract available